Using Biosocial Criminology to Understand and Improve Treatment Outcomes - Vaske, Jamie C. (Criminal justice and behavior, 2017)
Research has extensively cataloged the types of interventions that prevent and treat antisocial behavior across the life course. Despite our knowledge of which interventions “work,” there is a limited understanding of why these practices are effective and who does (or does not) benefit from traditional evidence-based practices (EBPs). The current study reviews the literature on the biopsychological mechanisms and moderators of EBPs across the life course, and it provides recommendations to clinicians and program developers based on these findings. The literature typically shows that EBPs may reduce antisocial behavior because these programs alter clients’ biological systems responsible for stress response and self-regulation. Similarly, individuals who receive fewer benefits from EBPs have weaker stress responses, difficulty processing punishment, increased reward sensitivity, and problems with attention, self-regulation, and cognitive flexibility. The implications of these findings are discussed for each stage of the life course.